Ethnographic Study of Acculturation on the “Timbung” War Tradition at Pejanggik Community in Central Lombok - Mansyur, Alif Ilman (IAIN Madura, 2023)
This study aims to explain: 1) the tradition history of the timbung war in sasak tribe,2) the acculturation of the timbung war tradition in the Pejanggik village community of Central Lombok, 3) the values contained in the timbung war tradition. Timbung war was carried out to reject reinforcements, and as a form of expression of gratitude to Allah SWT when viewed from its implementation, the timbung war has a lot of history, symbolism, and values. In this tradition celebration is developed by the community, and in its implementation contains social aspects, and acculturation. The acculturation that occurs in the timbung war tradition is a mixture that occurs between Islam and local cultural traditions that have existed for a long time and are preserved by the Pejanggik village community. The research method used is descriptive qualitative, this method aims to produce a descriptive data in the form of, writings, documents. In this study, it was found that the acculturation contained in timbung war is a mixture that occurs between Islam and traditions that have existed since long ago which are preserved by the Pejanggik Village community as one of the cultures and media to stay in touch with each other. In addition, some of the social values that included in acculturation are: 1) Respect, 2) Open-mindedness, 3) Empathy, 4) Communication, 5) Flexibility, 6) Collaboration, 7) Tolerance, 8) Cultural Awareness, and 9) Integration.